Automating the land valuation process carried out in land consolidation schemes - Demetriou, Demetris (My University, 2018)
Land consolidation is an effectual land management procedure aiming to sustainable development. A critical issue in land consolidation schemes is land valuation which is a type of mass appraisal that is generally carried out using an empirical process. As a result, the process is time consuming, costly and the outcomes are not adequately accurate, reliable and consistent. A solution to these problems is the employment of automated valuation models (AVMs). In this context, this paper presents the development, implementation and evaluation of two hedonic price models based on a linear and a non-linear function combined with a geographical information system (GIS), applied to a case study area in Cyprus. Models tested for quality assurance based on international standards. The evaluation based on international standards showed that the both models produced very good results and a small sample of land values provided by the Land Valuation Committee (LVC) is adequate to automate the land valuation process resulting in an adequate accuracy, reliability and consistency. Consequently, the AVM is highly efficient compared to conventional land valuation methods since it may considerably reduce the time and resources used and provide transparency because the process has been converted from empirical to systematic, analytical and standardized.
Keywords: Automated valuation models; GIS; Hedonic regression modeling; Land consolidation; Mass land valuation